2021
DOI: 10.1002/adom.202001954
|View full text |Cite
|
Sign up to set email alerts
|

Individual Si Nanospheres Wrapped in a Suspended Monolayer WS2 for Electromechanically Controlled Mie‐Type Nanopixels

Abstract: All‐dielectric (especially silicon) nanostructures that are capable of low‐loss sub‐wavelength light localization are favorable for miniaturized all‐optical or optoelectronic chips. Recently, Si waveguides have been integrated with the 2D transition‐metal dichalcogenides (TMDCs) with atomic thinness and intense light–matter interactions for high‐performance optoelectronic devices. However, further miniaturized and nanoscale optoelectronic devices are highly necessary and can be realized using all‐dielectric Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Extensive studies have been reported recently on heterostructures of dielectric nano cavities and TMDs and have demonstrated emission directionality control, [3,24,25] manipulation of single photon emission, [26] enhanced nonlinear effects, [27] and so on. [28][29][30] Compared to their plasmonic counterparts, the dielectric nanocavities have a larger effective mode volume, which competes with increasing their coupling constant. Despite this, their possession of the magnetic dipole (MD) mode can be advantageous to achieve a high coupling constant because an MD induces a tangential electric field on the core surface.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been reported recently on heterostructures of dielectric nano cavities and TMDs and have demonstrated emission directionality control, [3,24,25] manipulation of single photon emission, [26] enhanced nonlinear effects, [27] and so on. [28][29][30] Compared to their plasmonic counterparts, the dielectric nanocavities have a larger effective mode volume, which competes with increasing their coupling constant. Despite this, their possession of the magnetic dipole (MD) mode can be advantageous to achieve a high coupling constant because an MD induces a tangential electric field on the core surface.…”
Section: Introductionmentioning
confidence: 99%
“…The strain-tuning scattering of Si nanopixels can be further enhanced by optimizing the MD and ED modes. Recently, transition metal dichalcogenides (TMDs) with strong exciton transitions show intriguing Mie-exciton couplings with all-dielectric nanoresonators. , Moreover, the deformation of TMD few-layers under strain enables active control of the coupling with optical nanoresonators . In our experiments, wrinkles were formed through transferring WS 2 few-layers on stretching PDMS and then releasing it, as shown in Figure a.…”
Section: Resultsmentioning
confidence: 90%
“…54,55 Moreover, the deformation of TMD few-layers under strain enables active control of the coupling with optical nanoresonators. 56 In our experiments, wrinkles were formed through transferring WS 2 few-layers on stretching PDMS and then releasing it, as shown in Figure 3a. Due to the different elastic modulus and recovery ability between WS 2 flakes and PDMS substrate, periodic wrinkles were formed.…”
Section: Strain-driven Scattering Of Si Nanopixels On Wrinkled Wsmentioning
confidence: 99%
“…From both the experimental and numerically calculated spectra, a strong peak at the wavelength of 490 nm is observed, which corresponds to the magnetic dipole (MD) resonance according to the Mie theory. 31,32 For the NPs with a diameter of 150 nm (Figure 4b) this peak shifts to the wavelength of 605 nm, with the electric dipole (ED) resonance peak appearing at the wavelength of around 500 nm, while for the NP with a diameter of 220 nm (Figure 4c), there are also electric quadruple (EQ) and magnetic quadruple (MQ) modes appearing. To define peaks around 525 and 605 nm on the scattering spectra for the NPs with a diameter of 220 nm, we made multiple decomposition procedures, which show that that the peak at 605 nm corresponds to the magnetic quadruple resonance (MQ) and the peak at 525 nm corresponds to the electric quadruple (EQ) resonance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%